Targeted delivery of peptide functionalized nanoparticles for ameliorating myocardial infarction - N Abhirami; S Sudhina; Akash Chandran; Mahesh Chandran; Janeesh Plakkal Ayyappan (The Egyptian Heart Journal)
Abstract Background Myocardial infarction (MI) continues to pose a significant global healthcare burden despite advances in treatment options and their effectiveness. The incidence, prevalence, and mortality rates associated with MI are rising, emphasizing the need for improved therapeutic strategies. Traditional invasive surgical methods, aimed at recanalizing blood flow to the coronary arteries, have proven insufficient in fully addressing the complexities of MI. This ongoing challenge necessitates the exploration of novel approaches to enhance treatment efficacy and outcomes for MI patients. Main text One promising approach is the use of nanoparticle delivery systems for targeted therapy to the infarct site. When conventional methods fail to achieve adequate permeability and retention, nanoparticle strategies offer a potential solution. Functionalizing nanoparticles is a particularly effective technique, allowing these particles to conjugate with specific ligands. These ligands possess the intrinsic ability to selectively bind to receptors that are overexpressed or uniquely present at the infarct site, thereby conferring “smartness” to the nanoparticle constructs. This review delves into the various strategies employed in nanoparticle-ligand functionalization, highlighting the versatility and potential of these approaches. It provides a detailed cross section of several ligand classes, each with unique properties and binding affinities that make them suitable for targeted delivery in the context of MI. The focus is on identifying ligands that are either unique to the infarcted myocardium or significantly upregulated during MI, ensuring precise and efficient targeting of therapeutic agents. Conclusion In summary, while traditional surgical methods for restoring blood flow in MI patients remain important, they are not sufficient on their own. By leveraging the specificity of these ligands, nanoparticles can be directed precisely to the infarct site, enhancing the delivery and efficacy of therapeutic agents. This review underscores the need for continued research into nanoparticle-ligand functionalization strategies, aiming to improve outcomes for MI patients and reduce the global burden of this condition.